2007
DOI: 10.1021/jm070111+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of Selective, Nonpeptidic Inhibitors of Cathepsin S with an Unprecedented Binding Mode

Abstract: The substrate activity screening (SAS) method, a substrate-based fragment identification and optimization method for the development of enzyme inhibitors, was previously applied to cathepsin S to obtain a novel (2-arylphenoxy)acetaldehyde inhibitor, 2, with a 0.49 microM Ki value (Wood, W. J. L.; Patterson, A. W.; Tsuruoka, H.; Jain, R. K.; Ellman, J. A. J. Am. Chem. Soc. 2005, 127, 15521-15527). In this paper we disclose the X-ray structure of a complex between cathepsin S and inhibitor 2 which reveals an unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We therefore applied a substrate-based fragment approach called substrate activity screening (SAS) to the development of nonpeptidic inhibitors of caspases-3 and -6. In the SAS method, which has previously been applied to proteases of the papain family, (Brak et al, 2008; Inagaki et al, 2007; Patterson et al, 2006; Wood et al, 2005) weak binding nonpeptidic substrate fragments are identified, optimized, and then converted to potent inhibitors. Herein, we report the identification of three novel, nonpeptidic pan-caspase irreversible inhibitors that blocked proteolysis of Htt at caspase-3 and caspase-6 sites, suppressed Hdh 111Q/111Q -mediated toxicity, and rescued HttN90Q73-induced degeneration of rat striatal and cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore applied a substrate-based fragment approach called substrate activity screening (SAS) to the development of nonpeptidic inhibitors of caspases-3 and -6. In the SAS method, which has previously been applied to proteases of the papain family, (Brak et al, 2008; Inagaki et al, 2007; Patterson et al, 2006; Wood et al, 2005) weak binding nonpeptidic substrate fragments are identified, optimized, and then converted to potent inhibitors. Herein, we report the identification of three novel, nonpeptidic pan-caspase irreversible inhibitors that blocked proteolysis of Htt at caspase-3 and caspase-6 sites, suppressed Hdh 111Q/111Q -mediated toxicity, and rescued HttN90Q73-induced degeneration of rat striatal and cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
“…They have led to the identification of active substrates and the subsequent optimization of inhibitors for cruzaine (also known as cruzipain)49, a cysteine protease of Trypanosoma cruzi that is the causative agent of Chagas disease. Also, inhibitors of cathepsin S 50, which is implicated in autoimmune diseases, and inhibitors of the hepatitis C virus protease51 have been identified. Positional scanning methods and complete platforms for inhibitor screening were also developed for screening MMPs.…”
Section: Protease Inhibitor Drug Discoverymentioning
confidence: 99%
“…To overcome the stability issues of peptidic inhibitors, we screened several recently reported non-peptidic scaffolds from a large library of compounds that was initially designed to target cysteine cathepsins in mammals (Brak et al, 2008; Brak et al, 2010; Inagaki et al, 2007; Patterson et al, 2006; Wood et al, 2005). These inhibitors use a 2,3,5,6-tetrafluorophenoxyarylmethyl ketone (TFPAMK) reactive group, and the P1 and P2 residues are linked through a triazole ring (see Table 1 for structures).…”
Section: Resultsmentioning
confidence: 99%